Ojcostwo Boże i ojcostwo ludzkie w ujęciu św. Augustyna - Swoboda, Antoni (Vox Patrum, 2015)
The presented article consists of two main parts. The first one describes the characteristic elements of God’s fatherhood as it is seen by St. Augustine. Author of the study shows in this section Augustine’s teaching on God as a creator and parent. Author points as well to the manifestations of God’s actions towards man, to show finally the views of St. Augustine on the place of God in human life. The second part takes into the light the thoughts of Bishop of Hippo on human fatherhood and especially reveals his views on the relationship of the human fatherhood to God’s fatherhood and indicates a good of the procreation. In the last part of this section, the author presents an assessment of earthly fatherhood made by St. Augustine.